2010
DOI: 10.3171/2009.6.jns09133
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cranial repair after craniectomy

Abstract: The overall rate of complications related to cranioplasty after craniectomy is not negligible, and certain factors may be associated with increased risk. Therefore, when evaluating the need to perform a large decompressive craniectomy, the surgeon should also be aware that the patient is not only subject to the risks of the initial operation, but also the risks of subsequent cranioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
210
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(237 citation statements)
references
References 22 publications
12
210
3
6
Order By: Relevance
“…This is notably higher than reported previously 6) . In a series of 213 patients, Chang et al 6) reported that 13 patients (6.1%) experienced fluid collection complications. However, in this study, there was no explanation for either the definition of EFC or the fate of EFC.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This is notably higher than reported previously 6) . In a series of 213 patients, Chang et al 6) reported that 13 patients (6.1%) experienced fluid collection complications. However, in this study, there was no explanation for either the definition of EFC or the fate of EFC.…”
Section: Discussioncontrasting
confidence: 55%
“…1). We defined EFC as low density fluid in the epidural space on brain CT scan Data from recent studies have indicated that cranioplasty following decompressive craniectomy was associated with a high complication rates, ranged from 16.4% to 34% 4,6,8,12) . However, these studies mainly analyzed on major complications including infection, hematoma formation, and bone flap resorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7]12,17 Unfortunately, it is difficult to draw meaningful conclusions from these studies due to their small sample sizes.…”
mentioning
confidence: 99%